Pengaruh Kualitas Pelayanan Terhadap Kepuasan Masyarakat Pada Kantor Desa Nangahale Kecamatan Talibura - Scolastika Lidya Heret; Maria Silvana Mariabel Carcia; Nunsio Handrian Meylano (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The research aimed to (1) investigate the effect of service quality on community satisfaction and (2) determine the magnitude of that effect. The population of this research included 3,675 residents of the Nangahale Village Office. Using Slovin's formula, 97 respondents were selected. Data were gathered through surveys and evaluated through descriptive statistical methods. The hypothesis was tested using the t-test. The results of the descriptive analysis showed that the independent variable, namely service quality (X), was categorized as good with a perception score of 80.44, while the dependent variable, namely community satisfaction (Y). was categorized as fair with a perception score of 67.7. Based on the hypothesis testing (t-test), it can be concluded that the service quality variable (X) had a positive and significant effect on the community satisfaction variable (Y). This was evidenced by the calculated t-value, which was greater than the t-table value (3.7671.984). The results of the determination analysis indicated that the contribution of the service quality variable (X) to community satisfaction (Y) at the Nangahale Village Office, Talibura Sub-district, Sikka Regency was 30.1%, while the remaining 69,9% was explained by other variables not included in this research model.